Interventional Therapy for Upper Extremity Deep Vein Thrombosis - Carlon, Timothy A.; Sudheendra, Deepak (Seminars in Interventional Radiology, 2017)
Approximately 10% of all deep vein thromboses occur in the upper extremity, and that number is increasing due to the use of peripherally inserted central catheters. Sequelae of upper extremity deep vein thrombosis (UEDVT) are similar to those for lower extremity deep vein thrombosis (LEDVT) and include postthrombotic syndrome and pulmonary embolism. In addition to systemic anticoagulation, there are multiple interventional treatment options for UEDVT with the potential to reduce the incidence of these sequelae. To date, there have been no randomized trials to define the optimal management strategy for patients presenting with UEDVT, so many conclusions are drawn from smaller, single-center studies or from LEDVT research. In this article, the authors describe the evidence for the currently available treatment options and an approach to a patient with acute UEDVT.
Keywords: upper extremity deep vein thrombosis; Paget-Schroetter syndrome; thrombolysis; pharmacomechanical thrombectomy; interventional radiology